Etika in odgovornost osebja, zaposlenega v reševalni službi - Milčinski, Janez (Obzornik zdravstvene nege, 1977)
The guidelines of the professional ethics of the health workers are set by both, the Code of Ethics of the Health workers and by the Health Service Act. The author points out the importance of emergency assistance, which requires an appropriate medical equipment of health staff and health institutions. The extent and quality of this aid should attain a higher level than the one provided by a non-trained citizen. Next, the responsibility of the personnel during the transport of a casualty or an ill person is pointed aut. The author stresses the rights of the patient to treatment, as well as the rights of his relatives in case of his death or mental disturbances.